Perceived Social Support and Psychosocial Problems in Visually Impaired: A Mediating Role of Emotion-Focused Coping - Saleem, Sadia; Sultana, Safia (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To examine the mediating role of emotion-focused coping about perceived social support and psychosocial problems in individuals with visual impairment. METHODOLOGY: This cross-sectional research included 559 participants selected by purposive sampling from special educational and integrated institutes of Lahore, Islamabad, and Rawalpindi from January-June 2019. Informed consent was obtained from institutional authorities and each participant as well. Statistical Package for Social Sciences (SPSS) 21 Version was used to analyse data and Hayes Bootstrapping Approach was used to run mediation analysis. RESULTS: The sample comprised men 62% and women 38% with the age range of 16-28 (M=20.32, SD=3.51). Results indicate that a significant negative relationship was found among social support, psychosocial problems, and emotion-focused coping. Mediation analysis further shows that emotionfocused coping partially mediates the association between perceived social support and psychosocial problems in a visually impaired sample (? = -.35; p<.001). CONCLUSION: Social support is usually considered a protective factor against life stressors and is being positively associated with problem-focused coping, yet its positive effect can be mitigated if a person is using emotion-focused perceiving coping. This study highlighted that a person with visual impairment needs not only social support but also active coping skills to handle problems to improve their functioning. KEYWORDS: Social Support, Coping, Psycho-Social Problems, Visual Impairment